2012
DOI: 10.1103/physrevb.85.054516
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between anomalous quasiparticle scattering and unconventional superconductivity in the hidden-order phase of URu2Si2

Abstract: The pressure dependent electrical resistivity of URu2Si2 has been studied at high pressure across the first order phase boundary of Px where the ground state switches under pressure from "hidden order" (HO) to large moment antiferromagnetic (LAFM) states. The electrical transport in URu2Si2 at low temperatures shows a strong sample dependence. We have measured an ultra-clean single crystal whose quality is the highest among those used in previous studies. The generalized power law ρ = ρ0 + AnT n analysis finds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Detailed calculations were performed with the underscreened Anderson Model [15], using two degenerate 5f bands. The proposed mechanism should also be operative for transition metal compounds which is in accord with the hypothesis of Tateiwa et al [16], who suggested that ''Hidden Order'' of the type found in URu 2 Si 2 could also be responsible for the mysterious pseudo-gap phase seen in the high-temperature iron-pnictide superconductors.…”
supporting
confidence: 68%
“…Detailed calculations were performed with the underscreened Anderson Model [15], using two degenerate 5f bands. The proposed mechanism should also be operative for transition metal compounds which is in accord with the hypothesis of Tateiwa et al [16], who suggested that ''Hidden Order'' of the type found in URu 2 Si 2 could also be responsible for the mysterious pseudo-gap phase seen in the high-temperature iron-pnictide superconductors.…”
supporting
confidence: 68%
“…Figures 5(a) and 5(b) represent the A vs. γ 2 and |S /T | vs. γ plots, respectively, for various materials . Note that we refer the literature data, but the analysis for the Fermi-liquid behavior is a remaining issue [89,90]. Here, although the Kadowaki-Woods plot can be corrected by involving the degeneracies [91][92][93], both plots well explain the universal relations among those quantities for the correlated materials with a metallic carrier density.…”
Section: Relation In the Transport Coefficientsmentioning
confidence: 83%
“…It is also known that the electrical resistivity of Sr 2 RuO 4 is well described within the FL scheme [72], in which the resistivity is given as ρ(T ) = ρ 0 + AT ν with the exponent ν = 2. On the other hand, the determination of ν is delicate [80], and as seen in other correlated materials, ν apparently depends on the residual resistivity even in high-purity level [81]. It may be useful to examine the exponent in high-purity crystals [82].…”
Section: Resultsmentioning
confidence: 99%